Waiting for Müteferrika Glimpses on Ottoman Print Culture - Săbev, Orlin 1970- (Ottoman and Turkish studies, 2018)
Sabev investigates the first Ottoman/Muslim printer Ibrahim Müteferrika and his printing activity in the first half of the 18th century. By focusing on Müteferrika's western-formed mind-set, the book analyzes the influence of his printing enterprise on the transition from scribal tradition to print culture in the Ottoman Turkish/Muslim milieu.